Lifelong Learning Through the Prism of Educators - Korana Lisjak; Anita Zovko (Revija za Elementarno Izobraževanje)
Continuous professional development and training represent not only choices, but also an obligation and responsibility for every single educator. The aim of the research was to investigate the attitudes of educators working in kindergartens in seven counties of the Republic of Croatia, about the importance of lifelong learning. The research was conducted on a sample of 279 female educators, and a survey questionnaire was used as a measuring instrument. The results of the study indicate that educators are aware of the importance of lifelong learning and professional development. They emphasize that it enables them to develop competences and contributes to the improvement of their educational practice. The largest number of educators participate in professional training several times a year; they choose the form of training most often by the topic in which they are interested, and the form of professional training that best suits the needs of educators is the interactive workshop.